HYPERAMMONEMIA IS ASSOCIATED WITH INCREASING SEVERITY OF BOTH LIVER CIRRHOSIS AND HEPATIC ENCEPHALOPATHY - NAWAZ, A; MAAZ, .; BHATTI, R; SHAHZAD, A; HAQ, HU (Biological and Clinical Sciences Research Journal, 2024)
Hyperammonemia is a critical condition frequently observed in patients with liver cirrhosis and hepatic encephalopathy. Objectives: The study’s main aim is to find that hyperammonemia is associated with increasing severity of both liver cirrhosis and hepatic encephalopathy. Methods: This retrospective cohort study was conducted at DHQ Hospital Nowshera Khyber Pakhtunkhwa from January 2023 to June 2023. A total of 175 patients diagnosed with liver cirrhosis were included in the study. Data collection was performed using the hospital’s electronic medical records system. The variables collected included demographic data like patients’ age and sex and clinical data concerning the etiology of cirrhosis, Child-Pugh score, and MELD score. Results: The study included 175 patients with liver cirrhosis, with a mean age of 54.3 ± 12.7 years, of whom 64% were male and 36% female. The etiologies of cirrhosis were predominantly hepatitis C virus (45%), hepatitis B virus (30%), alcoholic liver disease (15%), and non-alcoholic steatohepatitis (10%). The mean Child-Pugh score was 8.7 ± 2.1, indicating moderate to severe liver disease, and the mean MELD score was 14.3 ± 4.5. The study found a strong positive correlation between ammonia levels and encephalopathy severity (r = 0.72, p < 0.001). Conclusion: It is concluded that hyperammonemia is significantly associated with the severity of liver cirrhosis and hepatic encephalopathy.